The last termination in the central South Atlantic. (1st September 2015) - Ljung, Karl; Holmgren, Sofia; Kylander, Malin; Sjolte, Jesper; Van der Putten, Nathalie; Kageyama, Masa; Porter, Charles T.; Björck, Svante
Abstract: Lake sediments and peat deposits from two basins on Nightingale Island (37°S), in the Tristan da Cunha archipelago, South Atlantic, have been analyzed. The studies were focused on the time period 16.2–10.0 cal ka BP, determined by 36 14 C dates from the two sequences. A wide variety of proxies were used, including pollen and diatom analyzes, biogenic silica content, C and N analyzes, stable isotopes ( 13 C and 15 N), elemental concentrations and magnetic susceptibility measurements, to detect environmental changes that can be related to shifts of the circulation belts of the Southern Ocean. In addition, climate model simulations were carried out. We find that the sediments are underlain by a >2 cal ka BP long hiatus, possibly representing a dried-out lake bed. The climate simulations corroborate that the area might have been exposed to arid conditions as a consequence of the Heinrich 1 event in the north and a southward displacement of the ITCZ. The development on the island after 16.2 cal ka BP is determined by the position of the Subtropical Front (STF) and the Southern Hemisphere Westerlies (SHW). The period 16.2–14.75 cal ka BP was characterized by varying influence from SHW and with STF situated south of Tristan da Cunha, ending with a humidity peak and cooler conditions. The stable conditions 14.7–14.1 cal ka BP with cool and fairly arid conditions imply that STF and SHW were both north of the islands during the first part of the Antarctic Cold Reversal. The most unstable period, 14.1–12.7 cal ka BP, indicates incessant latitudinal shifts of the zonal circulation, perhaps related to climate variability in the Northern Hemisphere and bipolar seesaw mechanisms as the strength of the Atlantic Meridional Overturning Circulation (AMOC) varied. At 12.7 cal ka BP the Holocene warming began with a gradually drier and warmer climate as a result of a dampened AMOC during the Younger Dryas cooling in the north with ITCZ, STF and SHW being displaced southwards. Peak warming seems to have occurred in the earliest part of the Holocene, but this period was also characterized by humidity shifts, possibly an effect of retraction and expansion phases of SHW during AMOC variations in the north. Highlights: We have data of the Last Termination from the central South Atlantic. We find evidence of bipolar see-saw effects at the latitude of 37°S. Our data imply a large southerly shift of the zonal circulation during Heinrich 1. We show that large shifts of the zonal circulation occurred 16.2 to 11 ka BP.